(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Pedagogical conditions for training future mathematics-informatics teachers are given in this thesis. Also, the mastering of new professional competences arising from the demands of the labor market, innovative activity, in a word, the development of professional competence are presented.